AKTIVIS ORGANISASI MAHASISWA SOSIOLOGI FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU - Dwie Mayang Sari; Achmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Activist student organization Sociology Faculty of Social and Political Sciences, Riau University. This research was conducted at the Department of Sociology, Faculty of Social and Political Sciences, University of Riau. The purpose of this study was to determine the extent of student activity in entering an intra-campus organization, the background of the student entering the organization, and the material and non-material benefits gained by activists. In terms of determining the informant using purposive sampling technique that is predetermined. The number of informants in this study were 6 people who were students who organized in the campus. The theory used is the Structural Functionalism (AGIL) theory of Talcott Parsons. The results of the study found that, overall the informants were very active in participating in the activities of intra-campus organizations, as well as students who entered the organization of their own desires. According to the informant, entering the organization must know the meaning and purpose of the organization. However, not all informants adapt in the organization according to the environment, there are those who still follow rather than their thoughts. The informant said that the goal when students enter the organization is not a waste because, students will get lots of new experiences that can be used as lessons, new knowledge that can be used after graduating from tertiary institutions or even can be sold very profitable in the future, and relations that are very helpful in the world of work going forward. Integration is carried out by activist students by maintaining their goal of achieving a unified whole. The pattern of maintenance carried out by the informant is to do the habits and norms that exist within the organization. The informant said that was their process of organizing to be able to play a role in their surroundings. Keywords: Activist, Students